NANo -OPERATORS AND NANO -CONTINUITY IN NANO TOPOLOGICAL SPACES - AHMED, NEHMAT K.; PIRBAL, OSAMA T. (Journal of Duhok University, 2023)
The aim of this paper is to introduce the notion of nano -operators in term of the class of nano -open sets such as nano -interior and nano -closure with their properties in nano topological spaces. After that, by using the class of nano -open sets, we introduce the concept of nano -continuity. Also, we study the relationship among some types of nano continuous functions in nano topological spaces